Spitz and Fisher's medicolegal investigation of death guidelines for the application of pathology to crime investigation - Spitz, Werner U. 1926-; Diaz, Francisco J. (Medical examiner); Fisher, Russell S. 1916-1984 (Charles C. Thomas Publisher, 2020)
"This is not just a new edition but a different book, emphasizing trauma and wound analysis. The addition of a new co-editor, Dr. Francisco J. Diaz, has brought new ideas to this fifth edition. A chapter by Doctor Jan Leetsma, world-renowned neuropathologist, has also been included. Doctor Leetsma's vast experience in forensic neuropathology will certainly enhance this book. Several chapters have been eliminated that are no longer applicable or which are adequately covered in other publications. Over time, in the past 48 years, since this book was first published, Medicolegal Investigation of Death has been dubbed the "Bible of Forensic Pathology." The fifth edition includes over 600 case reports and hundreds of color photographs. The cases are from files the authors have personally handled. According to author Spitz, "We have found many times analysis of small wounds will lead to understanding of a giant case-like the case in Hawaii, where a body was found under a full-size van, with a thread mark on the cheek consistent with having been hit with a black pipe used for gas lines that were found in a bucket in the rear of the van. As it turned out, this was a murder, not an accident." The book is full of such cases. This book will help you understand the details of injuries and how a person was injured and how they died and how these injuries, perhaps at first blush possibly seemingly insignificant, can shed new light on a case. Medicolegal Investigation of Death now embraces not just basic forensic pathology but also includes death during restraint, conscious pain and suffering and new concepts related to the interpretation of injuries by detailed wound analysis. The continued use of simple, non-technical terminology makes this book a truly unique treatise and source of information"--